BLOOD TYPE AND RHESUS FACTOR AS MARKERS OF SUSCEPTIBILITY TO SOME PATHOLOGIES IN IVANO-FRANKIVSK - Шум’яцька, Ірина; Сімчук, Андрій (SWorldJournal, 2022)
The marking effect of AB0 and Rh blood types were investigated at pathologies and in a norm among the men and women in age from 8 to 81 years, resident in territory of Ivano-Frankivsk сity. The marking effect for blood types in women were found in regard